2016
DOI: 10.1111/aogs.12894
|View full text |Cite
|
Sign up to set email alerts
|

Variations in rates of severe perineal tears and episiotomies in 20 European countries: a study based on routine national data in Euro‐Peristat Project

Abstract: The large variations in severe tears and episiotomies and the negative association between these indicators in 2010 show the importance of improving the assessment and reporting of tears in each country, and evaluating the impact of low episiotomy rates on the perineum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
115
2
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(138 citation statements)
references
References 24 publications
13
115
2
8
Order By: Relevance
“…Over the same period, severe perineal tears (third and fourth degrees) significantly increased in women who had non-operative vaginal deliveries. These results were consistent with those of the Euro-peristat project, which described an increase in the rate of severe perineal tears for all vaginal deliveries between 2004 and 2010 in all European countries, except Germany and Norway [28]. This issue is still the subject of a controversial debate [7, 9, 20, 2932].…”
Section: Discussionsupporting
confidence: 89%
“…Over the same period, severe perineal tears (third and fourth degrees) significantly increased in women who had non-operative vaginal deliveries. These results were consistent with those of the Euro-peristat project, which described an increase in the rate of severe perineal tears for all vaginal deliveries between 2004 and 2010 in all European countries, except Germany and Norway [28]. This issue is still the subject of a controversial debate [7, 9, 20, 2932].…”
Section: Discussionsupporting
confidence: 89%
“…According to a recent study comparing rates of episiotomy in 20 European countries found important differences, varying from 3,7% in Denmark to 75% in Cyprus [32]. In other institutes and in other countries in which episiotomy is practiced selectively, the present results are expected to encourage further studies to find answers to the more decisive questions: Is it time to stop performing episiotomies?…”
Section: Discussionmentioning
confidence: 52%
“…Remiantis A. Kudrevičienės ir kt. [16] analizės duomenimis, kai virkštelės kraujo pH <7,2 -tai traktuojama kaip acidozė, patvirtinanti, jog yra naujagimio hipoksija.…”
Section: Tyrimo Medžiaga Ir Metodaiunclassified
“…Remiantis Blondel B. ir kt. [16] duomenimis, III -IV laipsnio tarpvietės plyšimo dažnis Europos šalyse (Danijoje 4,8 proc., Estijoje 0,9 proc., Suomijoje 1,1 proc., Vokietijoje 1,8 proc., Islandijoje 4,9 proc., Švedijoje 3,5 proc., Olandijoje 2,7 proc., Jungtinėje Karalystėje 3,2 proc.) didesnis nei LSMUL KK Akušerijos ir ginekologijos skyriuje.…”
Section: Tyrimo Medžiaga Ir Metodaiunclassified